Pendugaan Umur Simpan Gula Kelapa Kristal dalam Kemasan Vakum menggunakan Metode Accelerated Shelf Life Test (ASLT) Model Arrhenius - Kavadya Syska; Nita Saniah Nuroniah; Ropiudin Ropiudin (Department of Agricultural Engineering, Syiah Kuala University, 2023)
AbstractCrystal coconut sugar contains reducing sugar in crystal coconut sugar which can cause crystal coconut sugar to be hygroscopic and make crystal coconut sugar easily absorb water. Efforts to slow down the rate of deterioration of crystal coconut sugar products can be done by packaging. Storage of crystal coconut sugar by vacuum packaging is an effort to inhibit the absorption of moisture from the environment so as to extend its shelf life. The aims of this study were 1) to examine the effect of storage and packaging temperature on several quality parameters of crystalline coconut sugar in vacuum packaging and 2) to develop the Arhenius Model Accelerated Shelf Life Test (ASLT) method to predict the shelf life of crystalline coconut sugar in vacuum packaging. This study used dried crystalline coconut sugar which was packaged using three different types of packaging, namely polyethylene (PE), vacuum packaging, and aluminum foil and then stored using different temperatures, namely 30°C and 15°C. then stored for 5 weeks and observed every 7 days. The results of calculations using the Arrhenius equation for the shelf life of crystalline coconut sugar with 2 storage temperatures and 3 different packages respectively, namely, PE packaging with a temperature of 30°C 1160 days and a temperature of 15°C 1697 days, vacuum packaging a temperature of 30°C 1504 days, temperature 15°C 2155 days, aluminum foil packaging temperature 30°C 7685 days and temperature 15°C 7690 days.Keyword : Shelf life, crystal coconut sugar, vacuum packaging, ASLT, arrheniusAbstrakGula kelapa kristal memiliki kandungan gula pereduksi yang dapat menyebabkan produk bersifat higroskopis dan mudah menyerap air. Upaya untuk memperlambat laju kerusakan produk gula kelapa kristal dapat dilakukan dengan pengemasan. Penyimpanan gula kelapa kristal dengan pengemasan vakum merupakan upaya untuk menghambat penyerapan uap air dari lingkungan sehingga dapat memperpanjang umur simpannya. Tujuan penelitian ini adalah 1) mengkaji pengaruh suhu penyimpanan dan kemasan terhadap beberapa parameter mutu gula kelapa kristal dalam kemasan vakum dan 2) mengembangkan Metode Accelerated Shelf Life Test (ASLT) Model Arhenius untuk menduga umur simpan gula kelapa kristal dalam kemasan vakum. Penelitian ini menggunakan gula kelapa kristal yang sudah dikeringkan kemudian dikemas dengan menggunakan tiga jenis kemasan yang berberda yaitu, kemasan polietilen (PE), kemasan vakum, dan alumunium foil kemudian disimpan dengan menggunakan suhu yang berbeda yaitu suhu 30°C dan 15°C, disimpan selama 5 minggu dan dilakukan pengamatan setiap 7 hari sekali. Hasil perhitungan menggunakan persamaan Arrhenius umur simpan gula kelapa kristal dengan 2 suhu penyimpanan dan 3 kemasan yang berbeda berturut-turut yaitu, kemasan PE dengan suhu 30°C 1160 hari dan suhu 15°C 1697 hari, kemasan vakum suhu 30°C 1504 hari, suhu 15°C 2155 hari, kemasan alumunium foil suhu 30°C 7685 hari dan suhu 15°C 7690 hari.